The design of multi-stage open-loop hollow fiber membrane contactor and its application in ammonia capture from hydrolyzed human urine. (1st December 2021) - Zhang, Junhui; Xie, Mengfei; Yang, Dandan; Tong, Xin; Qu, Dan; Feng, Li; Zhang, Liqiu
Highlight: A design method of multi-stage open-loop HFMC was proposed. Needed modules meeting the ammonia capture demand were accurately calculated. Effluent TAN and ammonia mass transfer coefficient of each module were predicted. Three-stage HFMC showed excellent ammonia capture efficiency of 93.29% . Abstract: Hollow fiber membrane contactor (HFMC) is a promising technology for removing or recovering wastewaters' volatile components. Developing a rational design method is very important for guiding its further application. In this study, we proposed a method to design the multi-stage open-loop hollow fiber membrane contactor (HFMC) employing shell-side influent. In addition, a three-stage HFMC was designed to capture ammonia from real hydrolyzed human urine. A continuous 1344 h performance was conducted. The results showed that the experimental effluent total ammonium nitrogen (TAN) concentration and ammonia mass transfer coefficient matched the predicted results well, which indicated that the design method was feasible and accurate. The three-stage HFMC showed excellent ammonia capture capacity with a TAN recovery efficiency of 93.29%, and the final effluent TAN concentration was 30.98±14.70 mg/L which met our design requirement (lower than 50 mg/L). More than 98.92% of the inorganic ions and 96.85% of the organic matter were retained in the effluent. The stripping solution after ammonia capture was the high-purity ammonium sulfate solution with low concentration of small molecular weight hydrophilic organic substances. The inorganic and organic membrane fouling was mild and randomly distributed. The inorganic membrane fouling was attributed to the deposition of calcium-, magnesium-, phosphate-related inorganic compounds, while the organic membrane fouling was mainly protein and carbohydrate. After the ammonia capture process, the surface hydrophobicity and pore properties of the membranes had no significant changes. These results demonstrated that the multi-stage open-loop HFMC could be a potential alternative for ammonia recovery from the high concentration of ammonium nitrogen wastewater. Graphical abstract: Image, graphical abstract